IDNLearn.com is designed to help you find reliable answers to any question you have. Find the solutions you need quickly and accurately with help from our knowledgeable community.
Sagot :
Answer:
Step-by-step explanation:
y = 4x + 11, and y = -2x - 1, so
4x + 11 = -2x - 1
6x + 11 = -1
6x = -12
x = -2
y = 4x+11 = 3
y = 4x + 11
y = -2x - 1
4x + 11 = -2x - 1
4x + 2x = -1 - 11
6x = -12
x = -12/6
x = -2
y = 4x + 11
y = 4(-2) + 11
y = -8 + 11
y=3
Answer is (-2,3).
Your participation is crucial to us. Keep sharing your knowledge and experiences. Let's create a learning environment that is both enjoyable and beneficial. Your questions deserve reliable answers. Thanks for visiting IDNLearn.com, and see you again soon for more helpful information.